Author correction: Why rankings of biomedical image analysis competitions should be interpreted with care - Maier-Hein, Lena; Eisenmann, Matthias; Reinke, Annika; Godau, Patrick; Feldmann, Carolin; Honauer, Katrin; Maier-Hein, Klaus H.; Neher, Peter; Stock, Christian; Kopp-Schneider, Annette (Nature Communications, 2019)
In the original version of this Article the values in the rightmost column of Table 1 were inadvertently shifted relative to the other columns. This has now been corrected in the PDF and HTML versions of the Article.
Gesehen am 15.10.2020
Correction to: Nature Communications;https://doi.org/10.1038/s41467-018-07619-7